2022
DOI: 10.1111/1756-185x.14545
|View full text |Cite
|
Sign up to set email alerts
|

Application of human data to predict hamstring tendon autograft diameter in Zhuang population

Abstract: Background: To explore the value of human data from the Zhuang population via predicting the diameter of the hamstring tendon autograft in anterior cruciate ligament (ACL) reconstruction and determining the feasibility of preoperative ultrasound for prediction. Methods:In total, 24 Zhuang patients who underwent ACL reconstruction with a 4-strand semitendinosus and gracilis tendon autograft (4 S-STG) were enrolled in this study. Before the operation, the affected semitendinosus tendon (ST) was examined by ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[16,19] There was no positive correlation between harvested graft diameter and body weight or BMI in the present study. Huang et al [30] concluded that body weight could predict graft diameter. Numerous factors influence body weight; sometimes, an individual has no control over some of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…[16,19] There was no positive correlation between harvested graft diameter and body weight or BMI in the present study. Huang et al [30] concluded that body weight could predict graft diameter. Numerous factors influence body weight; sometimes, an individual has no control over some of these factors.…”
Section: Discussionmentioning
confidence: 99%